إشكالية الهوية اللغوية والثقافية عند الشباب العربي وتجلياتها في التواصل اللغوي والاجتماعي /The Problem of Linguistic and Cultural Identity among Arab Youth and its Manifestations in Linguistic and Social Communication - Majdi Hajj Ibrahim; Muhammad Ismaili Alawi; Saeed Ali Al asla, (مجلة الدراسات اللغوية والأدبية (Journal of Linguistic and Literary Studies), 2023)
ملخص البحث: تعدّ الهوية وقضاياها من الإشكالات الحديثة في التداول الفكري الإنساني؛ إذ لا تخلو ثقافة من الثقافات المكونة للنسيج الإنساني على وجه البسيطة من سؤال الهوية ونسله. تصبح مسألة الهوية عامة، والهوية اللغوية اللغوية خاصة، قضية حساسة تثير الكثير من التساؤلات والنقاشات، وتتجلى انعكاساتها مباشرة على ألسنة الشباب؛ لأنهم الفئة الأكثر تأثراً بما يجري في محيطها المحلي والدولي، من هنا يأتي هذا المقال لمناقشة أهم التحولات التي شهدها العالم؛ لا سيما في ظل الثورة التكنولوجية المتسارعة في مجـال الاتصـال وتقنيـة المعلومـات والاستخدام الواسع لوسائل التواصل الاجتماعي، وآثارها الخطيرة على مسألة الهوية عامة، والهوية اللغوية خاصةً، لدى فئة الشباب والمراهقين العرب بوجه خاص. وتوصل البحث إلى أن تشكل قضية الهوية اللغوي في علاقتها بالتنمية الشاملة قضية مركزية وحساسة في سبيل تحقيق الهدف العام، وهو تعزيز الانتماء والفخر باللغة العربية، وبثقافتها وحضارتها وتراثها المجيد، وأن تحقيق التنمية الشاملة في مجالات الحياة المختلفة من شأنه أن يفرض على الشباب إعادة النظر إلى أوطانهم على أساس أنها أوطان توفر العيش الكريم لهم، وللأجيال القادمة، وأن الفرص الاقتصادية وهامش الحرية والتعبير عن الذات، وممارسة حقوق الإنسان، والتي لا يجدونها إلا في الدول الغربية يمكن أن يجدوها في بلدانهم، حينها سيتعزز لديهم الشعور بالأمان الذي هو الأساس لكل اعتقاد وتفكير وبناء للأوطان. الكلمات المفتاحية: الهوية، الثقافة، التواصل الاجتماعي، لغة الشباب. Abstract Identity and its issues are among the modern problems in the human intellectual circulation. All cultures that make up human identity in this world are not separated from the question of identity and lineage. The issue of identity, and linguistic identity particularly, becomes a significant issue that raises many questions and discussions. The impact was seen directly on the tongues of young people because they are the group most affected by what is happening in their local and international environment. On that basis, comes this article to discuss the most important transformations that the world has witnessed, especially in light of the accelerating technological revolution in the field of communication and information technology and the widespread use of social media. This study also looked into the serious effects on the issue of identity in general, and linguistic identity in particular, among Arab youth and adolescents in particular. The research concluded that the issue of linguistic identity in its relationship to comprehensive development is a central and sensitive issue in order to achieve the general goal, which is to enhance the sense of belongingness and pride in the Arabic language, its culture, civilization and glorious heritage. In order to achieve comprehensive development in various fields of life would require young people to reconsider their homelands. The basis is that they are homelands that provide a decent life for them and for future generations. They have to believe that economic opportunities and the margin of freedom, self-expression and the exercise of human rights, which they only find in Western countries, can be found in their own countries. Keywords: identity, culture, social communication, youth language. Abstrak Isu identiti adalah antara isu kontemporari yang sentiasa beredar dalam pemikiran manusia. Kesemua budaya yang membentuk jati diri manusia di dunia ini tidak terlepas dari persoalan jati diri dan keturunan. Isu identiti, terutamanya identiti linguistik, menjadi isu sensitif yang menimbulkan banyak persoalan dan perbincangan. Impaknya jelas terserlah secara langsung pada penggunaan bahasa golongan muda kerana mereka adalah golongan yang paling terkesan dengan persekitaran mereka, bermula dari kawasan tempatan sehinggalah ke peringkat antarabangsa. Atas dasar itu, kajian ini akan membincangkan perubahan-perubahan penting yang berlaku di dunia ini, terutamanya dari aspek revolusi teknologi yang semakin pantas dalam bidang komunikasi dan teknologi maklumat. Kajian juga akan melihat kepada kesan serius penggunaan media sosial secara meluas terhadap isu identiti, khususnya identiti linguistik, di kalangan belia dan remaja Arab khususnya. Penyelidikan merumuskan bahawa isu identiti linguistik dalam hubungannya dengan pembangunan menyeluruh adalah isu yang penting bagi mencapai matlamat umum, iaitu meningkatkan kekitaan dan kebanggaan terhadap bahasa Arab, budaya, tamadun dan warisan. Bagi mencapai pembangunan menyeluruh dalam pelbagai bidang kehidupan, ia memerlukan golongan muda untuk menanam sikap cinta kepada tanah air mereka sebagai tanah air yang menyediakan kehidupan yang layak untuk mereka dan untuk generasi akan datang. Mereka juga perlu yakin bahawa peluang pekerjaan, kebebasan bersuara dan hak asasi manusia, yang seringkali mereka kaitkan dengan negara Barat, boleh juga didapati di negara mereka sendiri. Kata kunci: identiti, budaya, komunikasi sosial, bahasa belia.